(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Asiatic Chrysomelidae Phaedon brassicae Baly is recorded for the first time in Italy. Introduced by plant trade, at present the insect has a limited diffusion. Being poliphagous and a pest on Brassicaceae in the native country, it could be a problem for various crops also in Europe.